Temperature-Sensitive Variants of an Established Myoblast Line - Loomis, W. F. (National Academy of Sciences, 1973)
Upon reaching confluency, mononucleated myoblasts fuse into multinucleated myotubes and concomitantly accumulate various characteristic muscle proteins, including myosin, actin, and several enzymes. We have approached the problem of determining the relationship between morphological and biochemical differentiation of muscle cells by isolating a series of temperature-sensitive clones from the established myoblast line, L(6). Twelve phenotypically variant clones were isolated from mutagenized populations of myoblasts. These fell into five classes, distinguishing conditional growth variants from conditional developmental variants. The phenotype of these strains, at least for the more extensively studied ones, was stable for more than 80 generations. Synthesis of characteristic proteins such as myosin, glycogen phosphorylase (EC 2.4.1.1), and phosphocreatine kinase (EC 2.7.3.2) has been studied in two conditional developmental mutants. One mutant, E(3), fuses into myotubes at 37° but not at 40°; the other, H(6), does not fuse into myotubes at 37° but does so at 40°. At permissive temperatures the enzymes accumulated in mutant cells with the same time course as in the parent cell line. Myosin accumulated in strain E(3) but not in strain H(6). At nonpermissive temperatures neither fusion into myotubes nor accumulation of any of the proteins occured in the cells of these two variant lines.